Effects of potato farming on small farmers’ food security in volcanic highlands of Rwanda - Aristide Maniriho; Ferdinand Nkikabahizi (Cogent Social Sciences)
This study investigated the role of potato cultivation in food security among small‑scale farmers in the Volcanic Highlands of Rwanda. Primary data were collected from a random sample of 401 farmers. Coarsened exact matching was employed to address potential selection bias between potato and non‑potato cultivators. A regression model was then estimated using maximum likelihood estimation. Results indicate potato producers are three times more likely to be food secure than other crop producers. Furthermore, potato farming demonstrated a statistically significant positive effect on food security for lower‑performing farmers, a non‑significant negative effect for moderately efficient farmers, and a non‑significant positive effect for high‑performing farmers. Specifically, lower‑performing potato farmers exhibited an eight times greater likelihood of food security compared to their counterparts cultivating other crops. This highlights the critical role of potato cultivation in ensuring food security for this subgroup. The study recommends strategies to enhance potato productivity and production, improve market access for stable agricultural prices and incomes, promote livelihood diversification to mitigate agricultural underemployment, leverage rural non‑farm income sources, and supplement farm incomes.